2015
DOI: 10.2147/ijn.s77858
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance hypointensive signal primarily originates from extracellular iron particles in the long-term tracking of mesenchymal stem cells transplanted in the infarcted myocardium

Abstract: Purpose The long-lasting hypointensities in cardiac magnetic resonance (CMR) were believed to originate from superparamagnetic iron oxide (SPIO)-engulfed macrophages during long-term stem cell tracking. However, the iron clearance capacity of the ischemic heart was limited. Therefore, we speculated that the extracellular SPIO particles may also be involved in the generation of false-positive signals. Methods and results Male swine mesenchymal stem cells (MSCs) were incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Most importantly, cellular labeling with magnetic nanoparticles do not allow for the reliable discrimination by MRI between live and dead cells, 10 , 31 though a long-term cell tracking (even up to 6 months) has been reported by using this method. 32 The MRI signal from magnetic particles may be compounded by the extracellular particles or particles engulfed by host macrophages if the transplanted cells died. 10 , 31 Moreover, the quantification of labeled cells by MRI is an indirect technique.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, cellular labeling with magnetic nanoparticles do not allow for the reliable discrimination by MRI between live and dead cells, 10 , 31 though a long-term cell tracking (even up to 6 months) has been reported by using this method. 32 The MRI signal from magnetic particles may be compounded by the extracellular particles or particles engulfed by host macrophages if the transplanted cells died. 10 , 31 Moreover, the quantification of labeled cells by MRI is an indirect technique.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main drawbacks associated with SPION is its inability to distinguish between viable and nonviable cells. Recently, Huang et al [ 34 ] showed that the long lasting MR signals were mainly generated by extracellular, instead of intracellular, iron particles. The high concentrations of extracellular SPIONs arose from iron extruded from injected cells and compounded with the lack of significant iron clearance in the myocardium.…”
Section: Challenges Of Stem Cell Imaging With Spionsmentioning
confidence: 99%
“… Schematic representation of generation and clearance of SPIONs in the myocardium (reproduced with permission [ 34 ]). …”
Section: Figurementioning
confidence: 99%
“…SPIO NPs can label stem cells in myocardium without affecting cell proliferation, differentiation, migration, and viability [ 68 , 69 ]. However, other studies demonstrated that MRI might overestimate survival rate of SPIO-labeled stem cells and could not track them for a long time, as macrophages within myocardium could phagocytose the discharged SPIO from the dead stem cells over time and result in false hypointensity on MRI [ 70 , 71 ]. Whatever, SPIO still can be applied to guide and assess the transplantation of stem cells into targeted tissue area [ 69 ].…”
Section: Nps For Stem Cell Trackingmentioning
confidence: 99%